1989
DOI: 10.1111/j.1471-0528.1989.tb01570.x
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenesis of genitourinary prolapse and stress incontinence of urine. A histological and histochemical study

Abstract: Summary. Histological and histochemical analysis of biopsy samples of pubococcygeus muscle obtained from asymptomatic women and from women with stress incontinence of urine, with or without genitourinary prolapse, have been coinpared. In the asymptomatic women both age and parity appeared to be related to the morphological features of the samples and in particular those obtained from the posterior part of the pubococcygeus. In the symptomatic women there was a significant increase in the number of muscle fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
119
3
10

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(142 citation statements)
references
References 12 publications
6
119
3
10
Order By: Relevance
“…5,6 In SUI, there is a decrease in the number of fast twitch fi bers. 7 Moreover, it has been observed that aging leads to reductions not only in the numbers of type I and II fi bers, but also in their diameter, thus increasing the prevalence of SUI among older women. 5 Clinical treatment for SUI is becoming more popular because of its excellent results, few collateral effects and decreased surgical and hospital costs.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In SUI, there is a decrease in the number of fast twitch fi bers. 7 Moreover, it has been observed that aging leads to reductions not only in the numbers of type I and II fi bers, but also in their diameter, thus increasing the prevalence of SUI among older women. 5 Clinical treatment for SUI is becoming more popular because of its excellent results, few collateral effects and decreased surgical and hospital costs.…”
Section: Introductionmentioning
confidence: 99%
“…Women with urinary stress incontinence seem to have a significant increase in denervation of the pelvic floor compared with asymptomatic women [50]. Postpartum partial denervation and reinnervation was confirmed by histomorphological studies [22].…”
Section: Pathophysiologymentioning
confidence: 79%
“…Difiere en cuanto a que la mayoría se encontraba en la postmenopausia pero sin terapia hormonal de reemplazo (8). En cuanto a la paridad promedio, el valor es elevado, considerando que este en un factor de riesgo importante para prolapso genital (15,16). Se obtuvieron resultados óptimos en un alto porcentaje.…”
Section: Discussionunclassified